Repeat caesarean sections: Complications and Outcome - Kobra, Khodeza Tul; Begum, Arzumanth Ara; Shova, Nazneen; Begum, Rashida (Journal of Dhaka National Medical College & Hospital, 2014)
Cesarean section is the commonest obstetric operative procedure worldwide. The incidence of cesarean section rate has been continuously increasing both in developed and developing world. A cesarean section poses some documented risks to the mother’s health in subsequent pregnancies. It is also associated with increased likelihood of preterm delivery, low birth weight and perinatal death. Objectives : The study was conducted to determine the incidence of maternal and neonatal morbidity and mortality in women with history of one or more previous caesarean section and to study the incidence of and type of surgical difficulties encountered in repeat cesarean sections. Methods : This prospective observational study was done in the department of Obstetrics &Gynaecology Dhaka National Medical Institute Hospital (DNMIH), Dhaka during the period from November 2008 to October 2009.A total number of 273 pregnant patients admitted with history of one or more cesarean sections were included in this study. Results : Out of the 1063 caesarean sections that were done during the study period 273 (25.68%) were repeat sections. Mean age of the study population was 27.2 years. Here 79.49% & 18.32% cases had history of previous one and two cesarean sections respectively. Important antepartum complications were chronic abdominal pain (16.49%), scar tenderness (6.6%), placenta praevia (1.47%), gestational diabetes mellitus (GDM) 1.47%, pregnancy induced hypertension (PIH) 7.7%, malpresentation (3.67%) etc. Emergency cesarean section was needed in 37.37% of cases. Blood transfusion required in 4.76% of cases. Extensive peritoneal adhesions with uterus and posterior surface of the anterior abdominal wall were found in 8.43% cases and bladder was adherent in 11.76% cases. In 5.88% cases take over of surgical procedure by senior obstetrician was necessary. Postoperative period was uneventful in 87.17% cases. Neonatal complications like prematurity, low birth weight, birth asphyxia and neonatal jaundice were developed in 21.62% of cases. Rate of perinatal mortality was 0.37%. Conclusions:Maternal and neonatal morbidity in repeated cesarean sections were low. Parietal wall and intra-peritoneal adhesions make repeat cesarean section a difficult procedure. It is prudent to involve a seniorexperienced obstetrician in the surgical procedure of repeat cesarean section. J. Dhaka National Med. Coll. Hos. 2014; 20 (02) : 11-15